The church as a moral agent in society: a case study of residents' perspectives of the role the church has played in the Kraaifontein residential area over the last ten years: 1994-2004 - Londt, Jonathan Robert (Department of Religious Studies, 2024)
This research assesses how residents in Kraaifontein, a semi-rural area in the Cape Peninsula vicinity, perceive the moral role that the church has played over a period of ten years from 1994 to 2004. The clergy and pastors of two mainline churches and two evangelical churches in Kraaifontein were chosen as the participants. They were asked to put forward the names of members of their respective church communities who have been consistently active within the life of the church and community for a period of approximately ten years. Criteria for selection were: a member of the church council, a youth, and a woman. The research methodology employed is a qualitative case study approach. Contextual data has been collected, including interviews, questionnaires and photographs. Inductive and deductive analyses have been made of emerging themes. Though the particular churches in the area may fulfill many other roles, the research focus is on the perceived role of the church as a moral agent in the area. This research has limitations. It does not examine the opinions of residents in the area who have not been involved in the church. These opinions may have been significant. It also does not examine what other functions the church is playing. The selection of interviewees may also have been favourably biased. Furthermore, other significant moral agents in the community, such as the schools, will not be examined. The sample will also be small and therefore will not be representative of the Kraaifontein area as a whole, nor the wider South African community. The research indicated that the church is seen to be at a crossroads in that the role that society feels the church needs to play differs from the role that the church would like to play.